Impact of Environmental Regulation on Green Technology Adoption by Farmers Microscopic Investigation Evidence From Pig Breeding in China - Lu, Yang; Tan, Yongfeng; Wang, Hongmei (Frontiers in Environmental Science, 2022)
Facing of increasingly serious resource and environmental constraints, the adoption of green technology has become the key to driving the green production transformation of farmers under the constraints of environmental regulation. Whether environmental regulation can improve the adoption of green technology in aquaculture still needs to be further tested. Based on the survey data of 544 pig farmers in Sichuan, Shandong, Henan and Hebei provinces, this paper first measures the adoption degree of green breeding technology by using the coefficient of variation method. Then, the econometric model is used to empirically test the relationship between environmental regulation and farmers' adoption of green technology. The results show that: firstly, environmental regulation can improve the adoption of green technology by farmers; Economic incentive regulation and educational guidance regulation can significantly improve the adoption of green technology by farmers from the perspective of environmental regulation, mandatory regulation. Secondly, environmental regulation has different effects on the adoption of green technology of different attributes of farmers. Its effect on the adoption of resource utilization technology is higher than that of harmless treatment technology and higher than that of reduction technology. At the same time, different dimensions of environmental regulation have different effects on the adoption of green technology by farmers with different attributes. Thirdly, the impact of environmental regulation on the adoption of green technology by different scale farmers is different, and its impact on high-scale farmers is more obvious. At the same time, different dimensions of environmental regulation have different effects on the adoption of green technology by farmers of different sizes.